Vitamin D receptor (VDR) contributes to the development of hypercalciuria by sensitizing VDR target genes to vitamin D in a genetic hypercalciuric stone-forming (GHS) rat model - Shang Guo; Weekai Chia; Hongwei Wang; David A. Bushinsky; Biao Zhong; Murray J. Favus (Genes and Diseases, 2022)
Human idiopathic hypercalciuria (IH) is the most common cause of calcium oxalate nephrolithiasis with perturbed calcium metabolism with increased bone resorption and decreased renal calcium reabsorption, which can be phenotype-copied in the genetic hypercalciuric stone-forming (GHS) rat model. We previously demonstrated that high VDR expression plays important roles in the development of hypercalciuria in the GHS rats. However, the underlying mechanism through which VDR impact hypercalciuria development remains to be fully understood. Here, we sought to determine how VDR regulated its target genes that are implicated in calcium homeostasis and potentially hypercalciuria. We found that VDR expression in the GHS rats was elevated in the calcium transporting tissues, as well as in the thymus and prostate, but not in lung, brain, heart, liver and spleen, when compared with control SD rats. Snail expression in the GHS rats was significantly downregulated in kidney, intestine, thymus and testis. Intraperitoneal injection of 1,25(OH)2D3 significantly upregulated the expression of renal calcium sensing receptor (CaSR), intestinal calcium transporters transient receptor potential vanilloid type 6 (TRPV6), and VDR in GHS rats, compared with that in control SD rats. ChIP assays revealed that VDR specifically bound to the proximal promoters of target genes, followed by histone H3 hyperacetylation or hypermethylation. Collectively, our results suggest that elevated VDR expression may contribute to the development of hypercalciuria by sensitizing VDR target genes to 1,25(OH)2D3 through histone modifications at their promoter regions in a genetic hypercalciuric stone-forming (GHS) rat model.